Specific Aspects Of The Political And Cultural Life Of The Kushan Empire - Khakimzhanova Zilola Gayratovna (Genius Journals, 2024)
The Kushan Empire, spanning from the 1st to the 3rd century CE, was renowned for its significant political and cultural contributions in Central and South Asia. The empire's unique blend of Greco-Roman, Persian, Indian, and Buddhist influences shaped its vibrant cultural life. Politically, the Kushans were known for their adept diplomacy, fostering trade along the Silk Road, and their strategic alliances with neighboring states. Culturally, they promoted religious tolerance, leading to the coexistence of various faiths such as Buddhism, Zoroastrianism, and Hinduism. The Kushan Empire's art and architecture flourished, with distinctive Gandharan art establishing a unique artistic identity. The Kushan rulers' support for art and literature led to an era of exceptional creativity, seen in their coinage, sculpture, and cave paintings.
Keywords: Empire; EmpireKushan estates; Yuechjes